Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s11682-019-00153-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron-regulatory genes are associated with Neuroimaging measures in HIV infection

Abstract: The pathogenesis of HIV-associated neurocognitive impairment (NCI) may involve iron dysregulation. In 243 HIV-seropositive adults without severe comorbidities, we therefore genotyped 250 variants in 20 iron-related genes and evaluated their associations with magnetic resonance imaging measures of brain structure and metabolites, including measures previously linked to NCI. Multivariable regression analyses examined associations between genetic variants and neuroimaging measures, adjusting for relevant covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…The biochemistry panel also included erythrocytes indices linked with iron metabolism (hemoglobin, mean corpuscular volume [MCV], mean corpuscular hemoglobin [MCH], and MCH concentration MCHC), serum total cholesterol, and triglycerides. The reason for investigating also these variables was based on previous evidence linking neuro‐inflammation, blood–brain barrier (BBB), cognitive performance, and iron metabolism (as erythrocytes indices) in PWH, 19–22 and on previous evidence of an interplay between lipids, BBB, and neurodegenerative processes in HIV‐negative populations 23–26 . Similarly, platelet count was also analyzed as previous studies have shown associations between platelets, HIV RNA replication, BBB dysfunction, and neuro‐inflammation 27–30 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochemistry panel also included erythrocytes indices linked with iron metabolism (hemoglobin, mean corpuscular volume [MCV], mean corpuscular hemoglobin [MCH], and MCH concentration MCHC), serum total cholesterol, and triglycerides. The reason for investigating also these variables was based on previous evidence linking neuro‐inflammation, blood–brain barrier (BBB), cognitive performance, and iron metabolism (as erythrocytes indices) in PWH, 19–22 and on previous evidence of an interplay between lipids, BBB, and neurodegenerative processes in HIV‐negative populations 23–26 . Similarly, platelet count was also analyzed as previous studies have shown associations between platelets, HIV RNA replication, BBB dysfunction, and neuro‐inflammation 27–30 …”
Section: Methodsmentioning
confidence: 99%
“…12,13 Furthermore, CNS is one of the main reservoirs contributing in the reactivation and peripheral reseeding of HIV when ART is interrupted, 14 and lastly, the identification of a subgroup of CSFC could be relevant to experimental cure strategies: PWH who better control HIV replication in CSF without ART might respond better to cure and MCH concentration MCHC), serum total cholesterol, and triglycerides. The reason for investigating also these variables was based on previous evidence linking neuro-inflammation, blood-brain barrier (BBB), cognitive performance, and iron metabolism (as erythrocytes indices) in PWH, [19][20][21][22] and on previous evidence of an interplay between lipids, BBB, and neurodegenerative processes in HIV-negative populations. [23][24][25][26] Similarly, platelet count was also analyzed as previous studies have shown associations between platelets, HIV RNA replication, BBB dysfunction, and neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Several neurologic disorders present with dysregulated cellular iron metabolism in the central nervous system, which can drive neuroinflammatory processes and disease progression (Rouault 2013 ; Porras and Rouault 2022 ). Brain iron metabolism has notably been examined in the context of Alzheimer’s (Lane et al 2018 ) and Parkinson’s (Mochizuki et al 2020 ) diseases, and more recently in neuroHIV (Pitcher et al 2014 ; Chang et al 2015 ; Patton et al 2017 ; Fennema-Notestine et al 2020 ), a neurologic disorder associated with HIV infection of select brain cells. Although HIV infection can be well-controlled by antiretroviral therapies, people living with HIV often develop mild to moderate cognitive impairment that can disrupt their daily life (Saylor et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iron plays a central role in innate immunity, and its regulation is critical for brain health [10]. The brain has a high metabolic demand for iron, since neuronal development, myelin synthesis and maintenance, and monoamine neurotransmitter synthesis require bioavailable iron; however, iron is also required for HIV replication [10, 11]. While essential for mitochondrial function and diverse metabolic processes, iron can mediate oxidative stress by catalyzing free-radical reactions and must therefore be tightly compartmentalized.…”
Section: Introductionmentioning
confidence: 99%